KEBIJAKAN DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KABUPATEN BOJONEGORO DALAM MELAKSANAKAN PERATURAN BUPATI NO. 59 TAHUN 2021 - Lestari, Ratna Ani; Darsono, Darsono; Machsa, Ali (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2023)
The problems in this research is licensing services, the process is quite long and has become a problem in the community. To carry out permits, it must go through requests and recommendations from related agencies, such as the building permit process (IMB) in Bojonegoro Regency. The purpose of this study is to describe and know DPMPTSP in implementing Regent Regulation No. 59 of 202. The theory in this study uses Edward III (1980) namely a) communication, b) resources, c) attitudes/dispositions, d) bureaucratic structure. This study uses a qualitative approach to analyze the extent to which Perbub No 59  year 2021 can be implemented. This research method includes a type of qualitative research. Collecting data in this study are observation, interviews, and documentation. The data analysis used is the interactive analysis model of Miles & Huberman (2014). The results of this study indicate that the Regent's Regulation No. 59 year 2021 has not fully implemented optimally, seen from: 1) in communication to coordinate between the offices of the Investment Service and Public Service Malls with the SKPD, staff at the DPMPTSP office are not given full authority by the SKPD head, 2) The existing resources are inadequate and competent, 3) attitudes/dispositions, namely the lack of collaboration between institutions, 4) The lack of coordination principles, therefore the principles of harmonious coordination are needed which is the key to unifying culture from each agency.